Relationships between substance use, anxiety, depression and stress by public university workers - Dilce Rejane Peres do Carmo; Daiana Foggiato de Siqueira; Amanda de Lemos Mello; Etiane de Oliveira Freitas; Marlene Gomes Terra; Ariane Naidon Cattani; Sandra Cristina Pillon (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To evaluate the relationship between psychoactive substance use, anxiety, depression and stress by workers at a Brazilian public university. Methods: This is a cross-sectional study with a quantitative approach, carried out with 345 workers from a public higher education institution, located in a city in the interior of the state of Rio Grande do Sul, Brazil. Results: Professionals with an average age of 38.9 years, 187 (54.2%) were women, 163 (47.2%) were single, 186 (53.9%) professed the Catholic religion, 223 (64.8%) had graduate school education. Of the workers, 122 (35.4%) considered their work to be stressful. The use of alcohol in the binge pattern (monthly) and heavy episodic drinking (weekly) were higher among workers with higher levels of anxiety, depression and stress. Conclusion: The use of alcohol in its different forms, stress, depression and anxiety show particularities that must be evaluated and recognized among the worker's health problems.